Foreign Concessions in Developing Natural Resources of Northeastern RSFSR in 1920s - N. I. Burnasheva; I. I. Kovlekov (Научный диалог, 2023)
This article examines the establishment of the state concession policy in the USSR during the 1920s, focusing on its objectives and principles, as well as its expansion into the northeastern regions of the Soviet state. The natural resources of the northeastern territories of Russia had attracted the attention of foreign concessionaires since prerevolutionary times, who established a network of trading representations for the procurement and export of furs, mammoth bones, fish, and various raw materials. In the 1920s, the Soviet state conducted significant work to prepare and approve legislative acts regulating concession activities and aimed at strengthening state influence over them. Special bodies were created to address these issues, including foreign trade departments (Vneshtorg), concession commissions (concesscom), and planning commissions. Through agreements between the Soviet government and foreign companies, concession activities began to yield practical results from the mid1920s. The principles on which it was based aimed to direct foreign economic relations towards the reconstruction of the country's economy. Overall, it can be concluded that the concession policy pursued by the USSR in the 1920s proved successful, playing a significant role in the reconstruction of the national economy after the civil war.